MiR-378a-3p Acts as a Tumor Suppressor in Colorectal Cancer Stem-Like Cells and Affects the Expression of MALAT1 and NEAT1 lncRNAs - Castellani, Giorgia; Buccarelli, Mariachiara; Lulli, Valentina; Ilari, Ramona; De Luca, Gabriele; Pedini, Francesca; Boe, Alessandra; Felli, Nadia; Biffoni, Mauro; Pilozzi, Emanuela; Marziali, Giovanna; Ricci-Vitiani, Lucia (Frontiers in Oncology, 2022)
MiR-378a-3p plays a critical role in carcinogenesis acting as a tumor suppressor, promoting apoptosis and cell cycle arrest and reducing invasion and drug resistance in several human cancers, including colorectal cancer (CRC), where its expression is significantly associated with histological classification and prognosis. In this study, we investigated the biological and cellular processes affected by miR-378a-3p in the context of CRC carcinogenesis. In agreement with the literature, miR-378a-3p is downregulated in our cohort of CRC patients as well as, in 15 patient-derived colorectal cancer stem-like cell (CRC-SC) lines and 8 CRC cell lines, compared to normal mucosae. Restoration of miR-378a-3p restrains tumorigenic properties of CRC and CRC-SC lines, as well as, significantly reduces tumor growth in two CRC-SC xenograft mouse models. We reported that miR-378a-3p modulates the expression of the lncRNAs MALAT1 and NEAT1. Their expression is inversely correlated with that of miR-378a-3p in patient-derived CRC-SC lines. Silencing of miR-378a-3p targets, MALAT1 and NEAT1, significantly impairs tumorigenic properties of CRC-SCs, supporting the critical role of miR-378a-3p in CRC carcinogenesis as a tumor-suppressor factor by establishing a finely tuned crosstalk with lncRNAs MALAT1 and NEAT1.